Impact of Canopy Openness on Spider Communities: Implications for Conservation Management of Formerly Coppiced Oak Forests - Košulič, Ondřej; Michalko, Radek; Hula, Vladimír (PloS one, 2016)
Traditional woodland management created a mosaic of differently aged patches providing favorable conditions for a variety of arthropods. After abandonment of historical ownership patterns and traditional management and the deliberate transformation to high forest after World War II, large forest areas became darker and more homogeneous. This had significant negative consequences for biodiversity. An important question is whether even small-scale habitat structures maintained by different levels of canopy openness in abandoned coppiced forest may constitute conditions suitable for forest as well as open habitat specialists. We investigated the effect of canopy openness in former traditionally coppiced woodlands on the species richness, functional diversity, activity density, conservation value, and degree of rareness of epigeic spiders. In each of the eight studied locations, 60-m-long transect was established consisting of five pitfall traps placed at regular 15 m intervals along the gradient. Spiders were collected from May to July 2012. We recorded 90 spider species, including high proportions of xeric specialists (40%) and red-listed threatened species (26%). The peaks of conservation indicators, as well as spider community abundance, were shifted toward more open canopies. On the other hand, functional diversity peaked at more closed canopies followed by a rapid decrease with increasing canopy openness. Species richness was highest in the middle of the canopy openness gradient, suggesting an ecotone effect. Ordinations revealed that species of conservation concern tended to be associated with sparse and partly opened canopy. The results show that the various components of biodiversity peaked at different levels of canopy openness. Therefore, the restoration and suitable forest management of such conditions will retain important diversification of habitats in formerly coppiced oak forest stands. We indicate that permanent presence of small-scale improvements could be suitable conservation tools to prevent the general decline of woodland biodiversity in the intensified landscape of Central Europe.
Keywords: Biodiversity; Animals; dub (rod); zachování přírodních zdrojů; zvířata; Quercus; Czech Republic; lesy; Spiders; biodiverzita; pavouci; Conservation of Natural Resources; Forests; Česká republika